MEMAHAMI BAHASA ALQURAN BERBASIS GRAMATIKAL (Kajian tehadap Kontribusi Pragmatik dalam Kajian Tafsir) - Fathurrosyid, Fathurrosyid (Jurnal At-Tibyan: Jurnal Ilmu Alquran dan Tafsir, 2018)
Interacting with the verses of the Quran by conducting analytical activities that stop at the linguistic context and its grammatical structure will not be sufficient to pursue the ultimate truth (maqasid asasiyah). Under such conditions, a secondary device is required to open layers of messages that are settled in text that can not be comprehensively understood from the grammatical perspectives of the text. The device in the study of linguistics is called pragmatic. Pragmatic presence in linguistic studies is context-dependent. The context intended in this pragmatic is not only the personalized context of the -particular (asbab al-nuzul khassah), but also the universal self-impersonal context (asbab al-nuzul ammah).Based on the above phenomenon, this research is about to reveal three important issues; First, what is the theory of pragmatics and pragmatics of the Quran ?.Secondly, how is the basic assumption of the Quranic pragmatics and the steps? Third, what are the contributions of pragmatic theory in the study of Quranic commentary ?. The goal, in addition to knowing the intent of pragmatic theory and pragmatics of the Quran, is also to unravel the basic assumptions of the Quranic pragmatics and what are their contributions in the study of tafsir.This research is library research. The primary data source is the Quran about the story of Maryam, while the secondary data is in the form of books of tafsir or books relevant to the theme of the story and pragmatic theory. The procedure is linguistic analysis using critical discourse analysis to reveal the ideology tucked behind the language and phenomenological analysis of the discourses that are told to dismantle the contribution of pragmatic theory in the study of the Quranic commentary.This study yields the following conclusions: First, the pragmatics of the Quran is a discipline that examines the QurÃ¢n from the standpoint of the relationship between the dyberic linguistic context; and triadic non-linguistic contexts. Secondly, the basic assumption of pragmatics of the Quran is because this scripture does not descend in empty space, but has a dialectical connection to Arab socio-cultural reality. In addition, the Quran is a holy book that uses the language media that is full of meaning and subjectivity of the mufassir. Thirdly, the contribution of prasetics in the study of Quranic interpretation shows that, (a) the presence of the theory of perlokusi as the instrument of determining the meaning of speakers whether in the form of declarative, imperative or other sentences. (b) implicatures as a deadlock solution of textual grammatical understanding and (c) the presence of pragmatics itself as a tool of understanding based on its context oriented to appropriateness in meaning and oriented appropriateness in form.